Outcomes of children, adolescents, and young adults following allogeneic stem cell transplantation for secondary acute myeloid leukemia and myelodysplastic syndromes—The MD Anderson Cancer Center experience. (3rd February 2017) - Maher, Ossama M.; Silva, Jorge Galvez; Wu, Jimin; Liu, Diane; Cooper, Laurence J.N.; Tarek, Nidale; Worth, Laura; Lee, Dean A.; Petropoulos, Demetrios; Franklin, Anna R.K.; Zweidler‐Mckay, Patrick; Wells, Robert J.; et al.
Abstract: We conducted a retrospective analysis of outcomes for children and young adults with sAML/sMDS who underwent HSCT at our institution. Thirty‐two patients (median age 20 years) with sAML (n=24) and sMDS (n=8) received HSCT between 1990 and 2013. The median time from sAML/sMDS diagnosis to HSCT was 4.1 months (range: 1.2‐27.2 months). The transplant regimens were primarily busulfan based (n=19). BM was the primary donor source (n=15). Eleven recipients were transplanted with residual disease. At a median follow‐up of 62.3 months (range: 0.4‐250.9 months), 14 patients had disease recurrence. Acute GVHD, grade III/IV, occurred in three patients. Causes of death were as follows: disease relapse (n=12), infection (n=2), pneumonia (n=1), pulmonary hemorrhage (n=1), acute GVHD (n=1), and graft failure (n=1). A PS of ≥90% at the time of HSCT had a significant impact on PFS ( P =.02). Patients achieving pretransplant primary CR (n=8) and those with sMDS and RA (n=6) had prolonged PFS ( P =.04). On multivariate analysis, shorter time to transplantation (≤6 months from diagnosis of sAML/sMDS) was associated with superior OS ( P =.0018) and PFS ( P =.0005).